Single Nucleotide Polymorphism (SNP) Arrays and Their Sensitivity for Detection of Genetic Changes in Human Pluripotent Stem Cell Cultures. Issue 11 (25th November 2022) - Steventon‐Jones, Victoria; Stavish, Dylan; Halliwell, Jason A.; Baker, Duncan; Barbaric, Ivana
Abstract: Human pluripotent stem cells (hPSCs) can be grown in culture indefinitely, making them a valuable tool for use in basic biology, disease modeling, and regenerative medicine. However, over prolonged periods in culture, hPSCs tend to acquire genomic aberrations that confer growth advantages, similar to those seen in some cancers. Monitoring the genomic stability of cultured hPSCs is critical to ensuring their efficacy and safety as a therapeutic tool. Most commonly employed methods for monitoring of hPSC genomes are cytogenetic methods, such as G‐banding. Nonetheless, such methods have limited resolution and sensitivity for detecting mosaicism. Single nucleotide polymorphism (SNP) array platforms are a potential alternative that could improve detection of abnormalities. Here, we outline protocols for SNP array whole‐genome screening of hPSCs. Moreover, we detail the procedure for assessing the SNP array's sensitivity in detecting low‐level mosaic copy‐number changes. We show that mosaicism can be confidently identified in samples only once they contain 20% variants, although samples containing 10% variants typically display enough variation to warrant further investigation and confirmation, for example by using a more sensitive targeted method. Finally, we highlight the advantages and limitations of SNP arrays, including a cost comparison of SNP arrays versus other commonly employed methods for detection of genetic changes in hPSC cultures. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : DNA sample preparation for SNP arrays Basic Protocol 2 : SNP array hybridization, washing, and scanning Basic Protocol 3 : SNP array data analysis Support Protocol : Assessment of SNP array sensitivity for detection of mosaicism